PELATIHAN PENGGUNAAN ZOOM DALAM KEGIATAN BELAJAR MENGAJAR DI SMK AVICENA RAJEG KABUPATEN TANGERANG - Yenni, Yenni; Fadillah, Ahmad; Baist, Abdul (Community Services and Social Work Bulletin, 2021)
The Covid-19 pandemic which has been endemic for several months, especially in Indonesia. As we all know, one of the consequences of this pandemic is that the government prohibits face-to-face learning in class. This prohibition applies to all levels. Therefore, we need the right media so that the teaching and learning process activities continue. The use of online media is the right choice. This is because in its use there is no need for direct contact between teachers and students. The chosen online application is Zoom where this application has many advantages that allow online learning to run interactively and maximally. The participants of this activity were all teachers of Avicenna Rajeg Vocational School, Tangerang Regency, Banten. In its implementation, lecturers are assisted by students with the aim of involving, introducing, and inviting students to interact in studying the material and its application in the real world. In general, the activity went smoothly, and participants were able to accept and understand the material presented by the lecturer.